Vaccination against COVID-19: the view of Brazilian federal judges - Wilson Medeiros Pereira; Fabrício Emanuel Soares de Oliveira; Maressa Lopes Coelho; Daniella Reis Barbosa Martelli; Hercílio Martelli Júnior (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: The aim was to analyze the perception of Brazilian federal judges on the implications of COVID-19 vaccination. A study was carried out with Brazilian federal judges, who received a survey designed with multiple-choice questions on COVID-19 vaccination, covering topics such as its mandatory aspect, the application of coercive measures, hesitation to vaccinate, priority groups, the duties of Brazilian Health Regulatory Agency (Anvisa, acronym in Portuguese), the role of the Judiciary branch, and immunity passports. A total of 254 out of 1,300 federal judges from all states responded to the survey. Most respondents have a Bachelor's degree or a specialization (59.1%) and have been judges for more than 10 years (63.8%). A great majority of the judges (87.7%) agree with vaccine mandates for adults and for children and adolescents (66.1%). Over 75% of judges believe that all levels of government can impose sanctions on those who refuse to get vaccinated. The judges trust vaccination 93% of the time, 56.1% reject anti-vaccination movements, and 75.2% believe that Anvisa duties should be respected. The Judiciary branch actions concerning the COVID-19 pandemic are approved by 62.6% of judges, and 88.2% support immunity passports. There is a direct connection among mandatory vaccination, trust in the vaccine, and the adoption of immunity passports. Most federal judges agree with vaccine mandates for children and adults, support the application of sanctions for vaccination refusal, disapprove of anti-vaccination movements, agree with Anvisa's duties, and support judicial intervention in relation to the COVID-19 pandemic.